A study on corporate social responsibility towards customer orientation in Malaysia / Naziah Ahmad Najib - Ahmad Najib, Naziah (Faculty of Business and Management, 2006)
Corporate social responsibility (CSR) has grown to play a significant and important role in directing and defining the way organizations do business. Corporate Social Responsibility will show how the companies conduct their business honestly and ethically. Besides that, we can see whether the companies have performed ethically in terms of their customers, employees, families, local community and society in ways that are goods for business and for development. Many businesses are gaining benefits from corporate social responsibility initiatives, with quantified improvements in revenue and market access, productivity, and risk-management. By conducting businesses honestly and ethically, the companies will maximize the company's profits and success in the long run. While a number of studies have explored the scope of corporate social responsibility and the role of management in allocating resources, given the recognized importance to business, few studies have empirically explored management conceptualizations of CSR in practice. Using structured interviews, this study explores 100 respondents from selected companies in Subang Jaya and Kota Bharu. This study reviews the understanding of the corporate social responsibility (CSR) concept and the issues that relates to CSR. This study is discusses since when companies conscious its responsibilities and factors. It is also done to know the opportunities that have arisen when assisting CSR towards customer from profit making to community service provider. Besides that, it is study to identify whether the companies have contributed any funds in terms of their social responsibility.